Personality and the nutritional habits of athletes using the example of the Polish national youth female wrestling team - Piepiora, P.; Superson, M.; Witkowski, K. (Archives of Budo Science of Martial Arts and Extreme Sports, 2017)
Background & Study Aim: A diet has a direct impact on a person`s body weight and is, therefore, very significant in combat sports, due to the existing division into weight categories. The purpose of this study was the relationship between specific personality traits and nutritional habits using the example of the Polish national youth female wrestling team.